1997
DOI: 10.1007/s002689900227
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐Guided Aspiration Biopsy for Detection of Nonpalpable Axillary Node Metastases in Breast Cancer Patients: New Diagnostic Method

Abstract: This study was designed to evaluate the accuracy of ultrasonography alone and in combination with fine-needle aspiration biopsy (FNAB) for detection of axillary metastases of nonpalpable lymph nodes in breast cancer patients. Ultrasonography was carried out in 150 axillas of 148 patients (mean age 57 years, range 30-80 years); and in 93 axillas lymph nodes were detected. Nodes were described according to their dimension and echo patterns and were compared with histopathologic results. FNAB was carried out in 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
188
7
8

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(226 citation statements)
references
References 27 publications
18
188
7
8
Order By: Relevance
“…We here reported a 16% false negative rate by US alone, since 28 out of 172 of US-nonsuspect LN were positive at histology. However, a great improvement of the diagnostic accuracy emerged when US examination was combined with FNAC of LN suspect to be metastatic, as demonstrated by the few available reports on the subject (Bonnema et al, 1997;Verbanck et al, 1997;de Kanter et al, 1999de Kanter et al, , 2000. In fact, in our study and in previous ones that used a similar approach, the cytological diagnosis of metastases reached 100% specificity.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…We here reported a 16% false negative rate by US alone, since 28 out of 172 of US-nonsuspect LN were positive at histology. However, a great improvement of the diagnostic accuracy emerged when US examination was combined with FNAC of LN suspect to be metastatic, as demonstrated by the few available reports on the subject (Bonnema et al, 1997;Verbanck et al, 1997;de Kanter et al, 1999de Kanter et al, , 2000. In fact, in our study and in previous ones that used a similar approach, the cytological diagnosis of metastases reached 100% specificity.…”
Section: Discussionsupporting
confidence: 54%
“…In fact, in our study and in previous ones that used a similar approach, the cytological diagnosis of metastases reached 100% specificity. On the other hand, Bonnema et al (1997) reported 80% sensitivity and a 76% negative predictive value of the cytological method. In the present work, we observed an increase in both sensitivity (89%) and negative predictive value (84%), which has to be related to the additional use of ICC.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In order to increase the specificity of preoperative assessment of the axilla, a number of groups have performed US-guided FNA (Bonnema et al, 1997;Verbanck et al, 1997;De Kanter et al, 1999;Krishnamurthy et al, 2002). Bonnema and de Kanter used this technique to detect axillary metastases in patients with operable breast cancer and preoperatively identified 63% (39 of 62) and 36% (31 of 87) of node-positive patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The range of sensitivity and specificity quoted in the literature for these techniques is such that the clinical management of the axilla cannot be modified for individual patients based upon these test results. US-guided fine needle aspiration (FNA) has been able to identify 36 -63% of node-positive patients preoperatively (Bonnema et al, 1997;De Kanter et al, 1999). Image-guided core biopsy has a higher sensitivity than FNA for assessing breast lesions (Britton and McCann, 1999), and therefore it would be anticipated that a similar improvement in sensitivity would be observed in USguided core biopsy of the axilla.…”
mentioning
confidence: 99%